The THE IMPACT OF DIFFERENTIATED LEARNING FOR EARLY CHILDHOOD - fauzia_herli noviampura; Irma Yuliantina; Isye Syoleha (International Conferences on Early Childhood Education Proceedings, 2023)
Currently, learning in early childhood is still dominated by teacher-centred learning, especially with the use of package books, student worksheets and magazines that homogenise children's activities in the classroom. This is also reinforced by the results of research on kindergarten teachers in Pesanggrahan District, South Jakarta, as many as 72.7% have not implemented differentiated learning. Differentiated learning includes approaches that are tailored to individual needs and abilities, so as to cater for the diversity of children in the classroom. In this context, teachers can provide different activities to each child, based on their interests, talents and developmental level. Thus, children can develop their imagination, problem-solving and critical thinking skills through fun and challenging learning. This research uses a qualitative descriptive method in which researchers conduct research on an object with natural or real conditions to create a systematic overview or detailed description that is factual and accurate. The implementation of differentiated learning encourages children to be more creative in expressing their ideas. Through this approach, children are given the opportunity to develop divergent thinking skills, be creative and innovate. Teachers can also provide developmentally appropriate challenges, activities that encourage children to think 'out of the box' and find unique solutions. In this learning process, children will feel more motivated and feel they have an active role in achieving learning goals. The results show that teachers who were trained in theory and practice can implement differentiated learning in their classrooms and show changes in children's abilities to be more critical, able to solve problems, convey ideas and be able to work together with their friends.